Quantitative EMG of external urethral sphincter in neurologically healthy men with prostate pathology. Issue 4 (12th August 2014) - Bianchi, Francesca; Cursi, Marco; Ferrari, Matteo; Salonia, Andrea; Amadio, Stefano; Comi, Giancarlo; Danuser, Hansjörg; Del Carro, Ubaldo; Mattei, Agostino
ABSTRACT Introduction There are no data on quantitative electromyography (EMG) of the external urethral sphincter (EUS) in men. The aim of this study was to obtain reference data from a group of neurologically healthy continent men with prostate pathology using a standardized technique. Methods: Sixty‐six subjects without neurological disorders were included. Motor unit potential (MUP) and interference pattern (IP) analysis were performed using multi‐MUP and turns/amplitude techniques, respectively. Results: Of 66 patients, 51 (mean age, 65.17; SD, 6.70) had localized prostate cancer (PCa), and 15 (mean age 61.67, SD 6.25) had benign prostate hyperplasia (BPH). Descriptive MUP parameters and IP‐clouds were obtained, respectively in the BPH and PCa groups. No group differences were found. Conclusions: This study provides quantitative EMG measures of EUS functionality in continent men with prostate pathology. The data could be used as reference values for patients undergoing prostate surgery to identify postoperative changes in EUS function possibly influencing continence. Muscle Nerve 50: 571–576, 2014